A systematic review of Rhinopetitia Géry (Teleostei, Characiformes, Characidae) with descriptions of four new species and redescription of R. myersi Géry - Menezes, Naércio A.; Netto-Ferreira, Andre L. (Zootaxa, 2019)
Rhinopetitia was known for a long time only by R. myersi, its type species, described from the Ilha do Bananal, Rio Araguaia basin, Tocantins, Brazil. Another recently described species, R. potamorhachia, was considered to differ from R. myersi by having the outer and inner rows of premaxillary teeth with seven to nine cusps, a midlateral dark stripe and a dark humeral blotch (versus outer and inner rows of premaxillary and of maxillary teeth with three to five cusps, and the absence of a dark midlateral stripe). Recently collected specimens from the Araguaia and Tocantins river basins are considered to belong to R. myersi, allowing to better characterize this species which is redescribed herein. Four new species are recognized for the genus, all from Brazil: 1) Rhinopetitia paucirastra, new species, collected from the upper Rio Tocantins drainage, state of Goiás, distinguished from all its congeners mainly by the presence of rudimentary and fewer gill rakers in external row on first gill arch; 2) R. oligolepis, new species originating from the Rio Jamanxim, Rio Tapajós drainage, state of Pará, differing from its congeners by having 4 longitudinal scale rows from dorsal-fin origin to lateral line; 3) R. melanohumeralis, new species, collected from small streams tributaries of the upper Rio Tapajós, and the upper Rio Xingu basins, states of Pará and Mato Grosso, that has the body as deep as in R. paucirastra but has well-developed and more gill rakers in the external row on first branchial arch; and 4) R. nigrofasciata, new species, collected in small tributaries of the upper portions of the Rio Tapajós and Rio Xingu basins, states of Pará and Mato Grosso, with the body narrower than in R. paucirastra and R. melanohumeralis.